Self-reported social impairments predict depressive disorder in adults with autism spectrum disorder. (February 2020) - Day, Talena C; McNaughton, Kathryn A; Naples, Adam J; McPartland, James C
In adults with autism spectrum disorder, co-occurring psychiatric conditions are prevalent, and depression is one of the most common co-occurring disorders. This study examined the relationship between depression and cognitive ability, autism symptom severity, and self-reported social impairments in autism spectrum disorder. A total of 33 adults with autism spectrum disorder and 28 adults with typical development completed a standardized psychiatric interview, cognitive test, measure of clinician-rated autism symptom severity, and self-report of social impairments. Nine participants with autism spectrum disorder (27%) met the criteria for a depressive disorder (autism spectrum disorder + depressive disorder). Relatively more females with autism spectrum disorder had a co-occurring depressive disorder. The typical development group had a higher intelligence quotient than the autism spectrum disorder group, but the autism spectrum disorder + depressive disorder group did not differ from the typical development or autism spectrum disorder group. While the autism spectrum disorder + depressive disorder group had lower clinician-rated autism symptom severity than the autism spectrum disorder group, the autism spectrum disorder + depressive disorder group reported more social impairments than the autism spectrum disorder group. Self-reported social impairments predicted depression in adults with autism spectrum disorder when accounting for symptom severity and cognitive ability. These findings suggest that more self-perceived social impairments are related to depressive disorders in autism spectrum disorder, and may help clinicians identify individuals who are vulnerable in developing a co-occurring depressive disorder. Future directions include follow-up studies with larger cohorts and longitudinal designs to support inferences regarding directionality of these relationships.